Exploring Mechanisms of Selective Directed Forgetting - Aguirre, Carmen; Gómez-Ariza, Carlos J.; Andrés, Pilar; Mazzoni, Giuliana; Bajo, Ma T. (Frontiers in Psychology, 2017)
While some studies have shown that providing a cue to selectively forget one subset of previously learned facts may cause specific forgetting of this information, little is known about the mechanisms underlying this memory phenomenon. In three experiments we aimed to better understand the nature of the selective directed forgetting (SDF) effect. Participants studied a List 1 consisting of 18 sentences regarding two (or three) different characters and a List 2 consisting of sentences regarding an additional character. In Experiment 1, we explored the role of rehearsal as the mechanism producing SDF by examining the effect of articulatory suppression after List 1 and during List 2 presentation. In Experiment 2 and 3 we explored the role of attentional control mechanisms by introducing a concurrent updating task after List 1 and during List 2 (Experiment 2) and by manipulating the number of characters to be selectively forgotten (1 out of 3 vs. 2 out of 3). Results from the three experiments suggest that neither rehearsal nor context change seem to be the mechanisms underlying SDF, while the pattern of results is consistent with an inhibitory account. In addition, whatever the responsible mechanism is, SDF seems to rely on the available attentional resources and the demands of the task. Our results join other findings to show that SDF is a robust phenomenon and suggest boundary conditions for the effect to be observed.